The influence of chronic diseases and multimorbidity on entering paid employment among unemployed persons – a longitudinal register-based study - Yildiz, Berivan; Burdorf, Alex; Schuring, Merel (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVES ': 'This study aimed to investigate the influence of chronic diseases and multimorbidity on entering paid employment among unemployed persons. A secondary objective was to estimate the proportion of persons not entering paid employment that can be attributed to specific chronic diseases across different age groups. ' ' METHODS ': 'Data linkage of longitudinal nationwide registries on employment status, medication use and sociodemographic characteristics was applied. Unemployed Dutch persons (N=619 968) were selected for a three-year prospective study. Cox proportional hazards analyses with hazard ratios (HR) were used to investigate the influence of six common chronic diseases on entering paid employment, stratified by age. The population attributable fraction (PAF) was calculated as the proportion of all persons who did not enter paid employment that can be attributed to a chronic disease. ' ' RESULTS ': 'Persons with chronic diseases were less likely to enter paid employment among all age groups. The impact of a chronic disease on maintaining unemployment at population level was largest for common mental disorders (PAF 0.20), due to a high prevalence of common mental disorders (6%), and for psychotic disorders (PAF 0.19), due to a high likelihood of not entering paid employment (HR 0.21), among persons aged 45–55 years. Multimorbidity increased with age, and the impact of having multiple chronic diseases on remaining unemployed increased especially among persons aged ≥45 years. ' ' CONCLUSION ': 'Chronic diseases and multimorbidity are important factors that reduce employment chances among all age groups. Our results provide directions for policy measures to target specific age and disease groups of unemployed persons in order to improve employment opportunities.
Keywords: chronic disease; employment; longitudinal; medicine; multimorbidity; PAF; population attributable fraction; register data; register-based study; unemployment